TERAPI NONFARMAKOLOGI NYERI PUNGGUNG BAWAH PADA IBU HAMIL : Literature Review - Herfina (2020)
Lower back pain in pregnant women is a physiological response from the mother's body that can have an impact on quality of life, sleep patterns, appetite, energy, daily activities and even emotional emotions of pregnant women if left untreated. Therefore it is important to manage lower back pain in pregnant women. To analyze various nonpharmacological therapies that effectively reduce lower back pain in pregnant women. This literature review uses an article search method with an electronic database database. Journal search using Google Scholar and PubMed. Search results found on Google Schoolar as many as 213 articles and PubMed as many as 397 articles. Article inclusion criteria taken include articles describing interventions to reduce low back pain in pregnant women, have a complete section, research articles published in 2015 - 2020. Nonpharmacological therapies to overcome lower back pain include massage therapy, kinesio tapping, Rose oil, acupressure, warm compresses and exercise. The most effective therapy is to do physical activity or sports. This literature review suggests conducting experimental research with interventions of physical activity or sports in pregnant women who complain of low back pain.